Rethinking the State in Africa: Perceptions of Nigerians on State Formation, State-Building, and a Negotiated Social Contract in the Nigerian Case. Issue 1 (2nd January 2023) - Isike, Christopher; Olasupo, Olusola
Abstract: The colonial disruption of organic state formation in Africa through the imposition of an alien state system adversely influenced state-building in the continent with consequences for good governance, belonging, and development in its holistic sense. Looking at the case of Nigeria, the adverse manifestations of the postcolonial state are signposted in the prevalent high level of insecurity that brings the state to the point of failure. This study used a mix of qualitative and quantitative research methods to interrogate the origins of the Nigerian state, the perverse character it manifests, and her future trajectory. The findings show that Nigeria is in self-destruct mode unless, for once, the fundamental problem of its imposed origin and essence is addressed. Doing so will require a political mechanism that enables Nigerians to participate in negotiating a social contract between the state and its citizens as equal stakeholders.